La SQRM 1980-2005 : Une première approche historique - Bail, Louise (Les Cahiers de la Société québécoise de recherche en musique, 2020)
En 2005, l’ARMuQ/SQRM fêtait son 25 e anniversaire d’existence. Répondant aux questions de la rédactrice en chef des présents Cahiers , Sylvia L’Écuyer, l’auteure expose d’abord les motifs qui ont poussé les membres fondateurs à créer ce qui s’appelait alors l’Association pour l’avancement de la recherche en musique du Québec (ARMuQ). Cette section est suivie d’un aperçu des différentes phases de l’évolution de l’association. Enfin, dans une troisième section intitulée « Problématiques et souhaits d’avenir », Louise Bail tente de dégager très brièvement les liens que l’ARMuQ/SQRM a développés avec les institutions d’enseignement supérieur et de circonscrire la place que prennent les chercheurs indépendants au sein de l’organisme. Son propos s’emploie à faire ressortir les problèmes particuliers que posent le fonctionnement et l’existence d’une telle association. Enfin, elle propose des réflexions et suggère quelques pistes d’avenir à partir de son implication en tant que membre fondateur, membre régulier et présidente sortante du conseil d’administration. , In 2005, the ARMuQ/SQRM celebrated its twenty-fifth anniversary. Responding to questions from the Cahier’s current Editor-in-Chief, Sylvia L’Écuyer, the author begins by discussing the motives that gave rise to the Association pour l’avancement de la recherche en musique du Québec, as it was then called. This is followed by a survey of the association’s various transformations over the years. In a third section entitled “Problématiques et souhaits d’avenir” (“Challenges and wishes for the future”), Louise Bail describes the ties that bind the ARMuQ/SQRM to post-secondary education institutions, and identifies the role of independent scholars within the organisation. The aim of her study is to discern the particular challenges that the existence and operations of such an association create. Finally, she reflects and advises on the association’s future from the perspective of her own role as founding member, regular member, and past Chair of the Board of Directors.

Recourir à la musique pour favoriser le bien-être et l’intégration des personnes réfugiées à Québec - Arsenault, Stéphanie; Moreno Sala, Maria (Nouvelles pratiques sociales, 2020)
Cet article porte sur une intervention musicale et interculturelle de groupe qui visait l’amélioration du bien-être psychologique et l’intégration des personnes réfugiées dans la ville de Québec. L’expérience a regroupé 20 personnes, dont 10 Québécois de longue date et 10 personnes réfugiées nouvellement arrivées, qui se sont réunies à 10 occasions pour échanger et jouer de la musique ensemble. Les propos recueillis avant, pendant et après la démarche démontrent que l’activité a contribué à l’amélioration du sentiment de bien-être des réfugiés, mais aussi d’une majorité des Québécois de longue date. Les propos montrent que la démarche a aussi contribué à l’intégration des réfugiés.
Keywords: Quebec; Québec; integration; intervention sociale; intégration; music; musique; refugee; réfugié; social intervention

Sounding the Arctic in Chantal Bilodeau’s Climate Change Plays - Balestrini, Nassim W. (Nordic Theatre Studies, 2020)
Quebec-born playwright Chantal Bilodeau has been responding to the challenges of dramatizing anthropogenic climate change by developing an eight-part Arctic Cycle, each play of which is set in one of the nations that claims Arctic territory. Sila (2014) immerses audiences into a complex network of humans, animals, and mythical beings crisscrossing the Canadian Arctic. These movements circle around the Inuit concept of sila, which is the life-giving force of breath and voice. Thus, the sonic world of Sila focuses on voices speaking words, on performance poetry, and on the sounds of breath and wind. Bilodeau’ s second Arctic Cycle play, Forward (2016), addresses the long-term impact of Fridtjof Nansen’s polar exploration of the 1890s on Norway’s economy and society. In terms of sound, Forward features multiple musical performances rangingfrom traditional songs to European opera arias and Lieder to contemporary Norwegian electro-pop. The sonic features of both plays stress interdependence across time, space, as well as (non-)human, earthly, and metaphysical realms. Sila and Forward address climate change in a non-universalizing manner which promotes a heterarchical (rather than hierarchical) aesthetic fit for a growing awareness of planetary relationality.
Keywords: Theory and practice

Gender and Embodiment in the Contemporary Montreal Swing Dance Community - Batty, Megan (Université McGill, 2020)
"This thesis explores embodiment and gender within the contemporary Montreal swing dance community. Drawing on scholarship in musicology, dance studies, jazz studies, and gender studies, I investigate the relationship between dancers and musicians/DJs. I explore the many facets of this choreomusical conversation and trace this dialogic and collaborative relationship on the social dance floor. The contemporary community is a product of the swing revival and navigating issues of authenticity thus becomes an important consideration for dancers, musicians, and DJs alike. One product of this revival is the set of heteronormative values that underpin the contemporary community. I investigate to what extent these values are reified, challenged, or altogether subverted by participants through musical and choreomusical choices. To this end I conducted interviews with six informants, each of whom has experience as both a dancer and musician and/or DJ. Their privileged position arising from their dual experience affords them insight on the ways in which dancers and musicians/DJs function within the community. This thesis builds on existing scholarship by situating the voices of individuals with choreomusical experience in dialogue with existing scholarship, and ultimately revalues the importance of both embodied knowledge and gender within the swing community"-- Author's abstract

Louise Campbell. Une médiatrice dans l’être - Bertomeu, Fanny (Revue musicale OICRM, 2020)
Formed as a musician and a clarinetist, Louise Campbell is now a music mediator. Based in Montreal, she practices her profession through several structures and for a wide variety of audiences (schoolchildren, professionals, people with disabilities ...) all around Canada, but mainly in Quebec. In this interview, Louise Campbell recounts her experience as a mediator, her (non)-formation in this profession, as well as many aspects in her practice. With the musical object and the creation at the heart of her workshops, Louise Campbell always seeks to establish a “horizontal” exchange relationship with each person she meets.
Keywords: Louise Campbell; creation; création; music mediation; médiation de la musique; partage; relation; relationship; sharing

“Maple Leaf Rag” in Maple Leaf Country: Impressing Jazz upon Vera Guilaroff - Blais-Tremblay, Vanessa (Women and Music: A Journal of Gender and Culture, 2020)

Pauline Julien, intime et politique (2018) - Carlos, Jean-Philippe (Bulletin d'histoire politique, 2020)

Bïa Krieger versionista: Três cançoes de Chico Buarque em francês [Bïa Krieger, versionista. Trois chansons de Chico Buarque en français] - Cassiano, Raissa Conde (Université de São Paulo, 2020)

TAGS de Joane Hétu et TanGRAM de Danielle Palardy Roger : signatures plurielles et figure continue - Dall’Ara-Majek, Ana (Circuit : musiques contemporaines, 2020)
TAGS by Joane Hétu and TanGRAM by Danielle Palardy Roger are two written works that showcase graphic scores in improvised music. TAGS creates an encounter between Ensemble SuperMusique, the saxophone quartet Quasar, and the Bozzini Quartet. The musicians make “sound graffiti” on an imaginary wall represented by a sequence of timed sections on a descriptive score where the composer uses different instrumental combinations. Using an aesthetic of articulated gestures, the work is made through these multiple signatures. TanGRAM brings together twenty instrumentalists from Ensemble SuperMusique. The game of Tangram is represented in the form of a graphic score where each piece has specific musical properties to be interpreted by the musicians. Rich in combinatorial and symmetrical games, the work presents Orion: a continuous figure, a slowly moving flow where each musician seeks their own way in a global sound.
Keywords: Analyse musicale; Danielle Palardy Roger; Joane Hétu; Musical analysis; graphic score; improvised music; musique improvisée; partition graphique

Visions multigénérationnelles de l’art sonore à Montréal - Dall'Ara-Majek, Ana (Circuit, 2020)
Partant d’une caractéristique de l’environnement artistique à Montréal - le décloisonnement des esthétiques et des formes d’expressions -, cette enquête compile les propos de six créateurs et artistes sonores de trois générations distinctes qui ont vécu ce contexte : Monique Jean et Jean-François Laporte (génération 1960), Patrick Saint-Denis et Cléo Palacio-Quintin (génération 1970), Adam Basanta et Émilie Payeur (génération 1980). Chacun se prononce sur quatre thématiques principales : la définition de leur pratique artistique, leurs réflexions sur la pluridisciplinarité ou la polyvalence, la perception de l’environnement artistique entre leurs débuts et aujourd’hui, et leur rapport à l’enseignement institutionnel versus l’apprentissage en autodidacte. Les réponses mettent en lumière la diversité des perceptions alimentant la diversité des pratiques, les sensibilités du contexte propres à chaque génération, ainsi que des visions personnelles de la ville quant à ses institutions et activités artistiques.

Blondie B, rappeuse des premières heures au Québec - Desfossés, Félix B. (Les racines du hip-hop au Québec. Tome 1, 2020)

Wavy Wanda et Baby Blue, pionnières du rap à Montréal - Desfossés, Félix B. (Les racines du hip-hop au Québec. Tome 1, 2020)

Mouffe. Au cœur du showbiz - Dumas, Carmel; Monfette, Claudine (Éditions La Presse, 2020)
La parolière d’Ordinaire et du Mur du son, c’est elle. La muse du jeune Charlebois, c’est encore elle. La metteure en scène de spectacles mythiques (Magie rose, J’ai vu le loup, le renard, le lion) et d’innombrables galas, c’est toujours elle. « Elle », c’est Mouffe, figure légendaire du Québec en marche, née Claudine Monfette, alouette ! Diplômée de l’École nationale de théâtre, interprète de chansons en duo et de rôles d’ingénue, éternelle tête chercheuse, semeuse de bonnes idées et mentore de la relève, elle a contribué à faire de notre milieu artistique ce qu’il est. Journaux personnels de Mouffe, entrevues avec celle-ci mais aussi avec sa famille, ses amis, ses collègues : Carmel Dumas a remonté pendant plus de dix ans le fil de cette vie palpitante et trace ici le portrait d’une femme omniprésente et effacée, fantaisiste et sage. Une vieille âme enveloppée de candeur, extraordinaire survivante.
Keywords: Biography & Autobiography / Artists, Architects, Photographers

Sacred Song Sisters: Choral and Solo Vocal Church Music by Women Composers for the Lenten Revised Common Lectionary - Elliott, Lisa A. (Université du Nevada, 2020)
This document explores sacred music by women composers for the Revised Common Lectionary (RCL) of the Catholic and Christian churches. The study researches exclusively choral and vocal solo music by women composers for the church season of Lent. Other primary limitations include music in English, and music from the nineteenth century to the present. The main question answered in this document is: what sacred music has been published by women composers that may be programmed in church services? This question is answered in the included appendices. These appendices list the music by women composers appropriate for the specific RCL readings for each Sunday of Lent, as well as the holidays of Ash Wednesday, Maundy Thursday, and Good Friday. There are also appendices of choral and solo vocal pieces that are generally appropriate for the Lenten season. Every attempt was made to be as thorough as possible in identifying this music, with the understanding that no one compilation of this kind can ever be complete. Additionally, selected works by six composers are explored in this document: Emma Lou Diemer (b. 1927), Arletta O’Hearn (b. ca 1928), Jane M. Marshall (1924 – 2019), Rebecca Clarke (1886 – 1979), Violet Archer (1913 – 2000), and Undine Smith Moore (1904 – 1989). These composers are representative of the variety of styles, diversity, history, and levels of musical complexity within this body of music.
Keywords: Choir; Christ; Female; Service; Sing; Worship

Renée Claude. Donne-moi le temps - Girard, Mario (Éditions La Presse, 2020)
À l’aube des années 1960, Renée Claude fait ses débuts de chanteuse en interprétant Ferré, Béart et Brassens, mais aussi, et surtout, les siens (Ferland, Léveillée, Vigneault, DesRochers, Lelièvre). Sa rencontre avec l’auteur-compositeur Stéphane Venne, puis son association avec le parolier Luc Plamondon marqueront un point tournant dans sa carrière. Pendant plus d’une décennie, Renée Claude enchaînera les succès. « C’est notre fête aujourd’hui », « Le début d’un temps d’un nouveau », « Le tour de la terre », « Viens faire un tour », « Tu trouveras la paix », « Un gars comme toi », « Ce soir je fais l’amour avec toi » ... Au début des années 1980, alors que d’autres chanteuses de sa génération rendent les armes, Renée Claude connaît une incroyable renaissance avec un cycle d’hommages à Clémence DesRochers, Georges Brassens et Léo Ferré. Offerts aux quatre coins du monde pendant plus de 30 ans, ces spectacles confirmeront son grand talent d’interprète. Grâce à des dizaines d’entretiens, le journaliste Mario Girard retrace le fascinant parcours de plus de 50 ans de cette artiste incomparable. À travers son histoire, il raconte aussi celle du Québec qui a émergé de la Grande Noirceur pour se tailler une identité à sa mesure. Et on peut affirmer que Renée Claude y a largement contribué.
Keywords: Biography & Autobiography / Entertainment & Performing Arts; Biography & Autobiography / General; Biography & Autobiography / Music

Identités de position queer dans la musique populaire au Québec - Girard, Stéphane (QuébeQueer. Le queer dans les productions littéraires, artistiques et médiatiques québécoises, 2020)
En plus d’offrir un portrait des productions culturelles queer au Québec tant francophones qu’anglophones, dont certaines autochtones, cet ouvrage s’attarde à révéler le caractère queer de celles qui ne le sont pas de facto. Il se présente comme un manuel de référence sur le sujet, avec des essais critiques – qui portent autant sur la littérature et le monde du spectacle que sur les arts médiatiques ou la presse gay – et des textes expérimentaux – fictions, dessins, récits autobiographiques. Plus de 27 œuvres de fiction publiées entre 1965 et 2017 y sont analysées sous différents aspects, avec des méthodologies diverses, mais toujours sous l’éclairage queer (un terme à la nature instable, paradoxale, que calque la forme éclatée de l’ouvrage). Du polyamour à l’inceste, en passant par le racisme, l’urbanité, le suicide, le non-désir d’enfant, l’alimentation ou les processus de production, le queer met en scène des personnages hétéros ou homosexuels, intersexués, cis, trans, travailleur·euse·s du sexe, gros et plusieurs autres… Cette juxtaposition d’états, de genres, de thèmes, de formes et de pratiques constitue l’une des forces de ce livre qui intéressera bien sûr un lectorat d’intellectuel·le·s et de personnes issues des communautés LGBTQIA2S+, mais pas seulement. Il deviendra, sans nul doute, une ressource indispensable pour l’enseignement de nouvelles perspectives dans le cadre des sciences humaines et sociales.

Resoundingly Entangled: Ageing and Memory in Étoile des aînés in Quebec - Grenier, Line; Sawchuk, Kim; Valois-Nadeau, Fannie (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)

College Boy (2013) de Xavier Dolan : pérenniser “le backward feeling” - Hakeem, Hasheem (Contemporary French Civilization, 2020)
En 2013, Xavier Dolan, cinéaste, acteur et metteur en scène québécois prolifique, réalise le vidéoclip College Boy, chanson du groupe de musique français Indochine qui s’articule autour d’un jeune garçon queer qui est victime d’homophobie dans un internat. Cet article propose une analyse de ce vidéoclip en se focalisant sur la mise en scène de la violence et des affects négatifs. Nous étudions d’abord le débat provoqué par la diffusion et la censure du clip en France. Ensuite, à partir de la théorie du “backward feeling” développée par Heather Love dans Feeling Backward: Loss and the Politics of Queer History (2007), nous analysons la manière dont la représentation de la violence dans l’œuvre de Dolan remet en question l’ordre hétéronormatif. Nous défendons la thèse qu’en s’attaquant de front aux institutions qui sont les véritables agents de la violence homophobe, College Boy contribue à la conservation archivistique de l’expérience queer et crée ainsi une possibilité d’émancipation face à l’hétéronormativité.

Jocelyne Binet's Cycle de Mélodies: Unearthing a Forgotten Song Cycle - Hoch, Matthew (Journal of Singing, 2020)
Montreal composer Jocelyne Binet's "Cycle de Melodies sur des Poemes de Paul Eluard" was programmed in 1955 by the French baritone Gerard Souzay in a performance that was most likely the world premiere. Unfortunately, Binet's song cycle never was published, and the work soon was forgotten. In the fall of 2016, the author discovered Bineet's original handwritten manuscript pages in holdings of Bibliotheque et Archives Nationales du Quebec and began the process of reconstructing the score. This article discusses the editorial journal undertaken when resurrecting Binet's forgotten song cycle, which was subsequently published in 2018 by Classical Vocal Reprints.
Keywords: Archives & records; Education; French language; Manuscripts; Music; Musical performances; Online data bases; Piano; Spelling; Vocal music

(Re)Presenting Indigenous Activism in the Nation's Capital: Signifying Resistance across Time and Place through Music in Alanis Obomsawin's Trick or Treaty? (2014) - Hoefnagels, Anna (Contemporary Musical Expressions in Canada, 2020)

Music, Geography and the Greatest Rewards: A Geohistorical Analysis on the Prestigious Awards of Céline Dion - Iconic Artist - Jucu, Ioan-Sebastian (Review of Historical Geography and Toponomastics, 2020)
In the present academic research connecting geography and music,a real gap remains in the study of different issues associated with both music and geography and, particularly, to the recent music geographies. This paper advances a new geographical approach in music geography highlighting the relevance of time and space in music, in the artist‟s outstanding contribution to music and in their recognition from the local to the global. Particularly the study is focused on one of the most emblematic music artists of the world, analyzing through a spatio-temporal investigation the prestigious awards achieved by the singer Celine Dion, since this singer remains both a real music legend and an iconic artist gaining multiple awards and thoroughly appreciated and admired for her outstanding contribution to music and global popular culture. The research bases on such specific methods as internet research, visual methodologies, bibliographical analysis and geographic information systems (GIS). The latter is used to provide a professional map illustrating the spatio-temporal distribution of the multiple awards received by Dion the artist. The findings of the research highlight the highest scale of appreciation an artist can receive. The results of the study also suggest that the outstanding contribution of the greatest artists of the world, acknowledged by the highest national, international and global forums, provide significant information about their artistic involvement in the global popular culture. They have a strong relevance both in space and in time, thus labeling different cultural decades and distinct places and spaces throughout the world.

Chaakapesh - Kingsley, Justin; Frappier, Roger (Fragments Distribution, 2020)
L'Orchestre symphonique de Montréal et son célèbre maestro Kent Nagano partent en tournée dans la grande toundra nordique du Québec pour visiter les communautés cries, innues et inuites, et partager avec eux un opéra de chambre autochtone où l'on apprend à l'homme blanc à rire et, par le fait même, à aimer davantage. Chaakapesh le périple du Fripon - écrit par Tomson Highway, composé par Matthew Ricketts et interprété par l'Orchestre symphonique de Montréal - est l'exemple le plus probant et moderne de collaboration interculturelle.

Death and Fairy Tale: Queer Autothanatography in Claude Vivier - Kingston, Andrew (differences, 2020)

Représentations du féminin et énonciation lyrique dans la chanson québécoise contemporaine : perspectives sur le sexe/genre chez Ariane Moffatt, Pierre Lapointe et Philémon Cimon - Konaté, Khady (Université d'Ottawa, 2020)
Cette thèse se propose de faire une analyse du discours sur les représentations du féminin et les implications du sexe/genre dans la chanson québécoise contemporaine, à travers les œuvres et la persona de trois auteur·ice·s-compositeur·ice·s-interprètes (ACI): Ariane Moffatt, Pierre Lapointe et Philémon Cimon. Notre analyse part d’abord du constat que les chansons de Moffatt, Lapointe et Cimon figurent des sujets lyriques, dont la parole et le geste sont modulés par les enjeux énonciatifs que posent le lyrisme. Pour rendre compte de la spécificité de la chanson comme pratique poétique réunissant paroles, musique et interprétation, nous proposons de faire une étude sémantique des chansons pour chacun·e des ACI, en nous attardant dans un premier temps aux questions soulevées par le lyrisme, puis en faisant la somme des aspects relevant du sexe/genre présents dans leurs univers sonores respectifs avec le renfort de la théorie féministe et des études de genre, d’après une perspective postmoderne. Notre lecture cherche à souligner les reconduites et les poncifs liés au féminin, mais également à saisir les propositions et les configurations qui s’écartent des lieux communs, tant pour les modèles féminins valorisés que pour les modèles amoureux et les rapports sociaux de sexe et de genre suggérés par les chansons. La comparaison entre les chansons des trois artistes permet ainsi de dégager des points de convergence, tout en révélant les particularités de leurs œuvres.

Monique Leyrac : notre grande dame de la chanson québécoise du XXe siècle - Laberge, Yves (Cap-aux-Diamants : la revue d'histoire du Québec, 2020)
Un article de la revue Cap-aux-Diamants, diffusée par la plateforme Érudit.

Céline, es-tu queer ? - Leblanc, Thomas (QuébeQueer. Le queer dans les productions littéraires, artistiques et médiatiques québécoises, 2020)
En plus d’offrir un portrait des productions culturelles queer au Québec tant francophones qu’anglophones, dont certaines autochtones, cet ouvrage s’attarde à révéler le caractère queer de celles qui ne le sont pas de facto. Il se présente comme un manuel de référence sur le sujet, avec des essais critiques – qui portent autant sur la littérature et le monde du spectacle que sur les arts médiatiques ou la presse gay – et des textes expérimentaux – fictions, dessins, récits autobiographiques. Plus de 27 œuvres de fiction publiées entre 1965 et 2017 y sont analysées sous différents aspects, avec des méthodologies diverses, mais toujours sous l’éclairage queer (un terme à la nature instable, paradoxale, que calque la forme éclatée de l’ouvrage). Du polyamour à l’inceste, en passant par le racisme, l’urbanité, le suicide, le non-désir d’enfant, l’alimentation ou les processus de production, le queer met en scène des personnages hétéros ou homosexuels, intersexués, cis, trans, travailleur·euse·s du sexe, gros et plusieurs autres… Cette juxtaposition d’états, de genres, de thèmes, de formes et de pratiques constitue l’une des forces de ce livre qui intéressera bien sûr un lectorat d’intellectuel·le·s et de personnes issues des communautés LGBTQIA2S+, mais pas seulement. Il deviendra, sans nul doute, une ressource indispensable pour l’enseignement de nouvelles perspectives dans le cadre des sciences humaines et sociales.

Les pratiques artistiques des personnes sourdes ou handicapées au Canada - Leduc, Véro; et autres (Conseil des arts du Canada, 2020)

Venus On Venus: CKUT’s Women’s Collective Music Show Dishes on Feminist Radio - Leventhal, Anna; McInnis, Catherine; Wilson, Angela (Women in Radio: Unfiltered Voices from Canada, 2020)
Three volunteer hosts and programmers of a feminist music show at a campus-community radio station, Anna Leventhal, Catherine McInnis, and Angela Wilson, sat down in 2008 to chat about feminist radio. They discussed the concept of a feminist music show and the possibilities and limitations of female-only spaces; the “fem-con” concept that campus-community radio stations be mandated to play a certain amount of music by women, in the same way they are mandated by the CRTC to play Canadian content; the transformative social and political potential of community radio; and the inclusion of trans and gender-nonconforming voices on the show.

Ageing with Waves: The Im/material Worlds of Two Quebec Ondists - Madden, David (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)
Ageing and memory - two aspects of life everybody has to face eventually. The contributions to this volume explore the cultural mediations of these categories. Through a series of approaches focused on practices and acts of memory, narratives, reminiscence, representation and collective memory, they seek to better understand and critically reflect on how ageing is experienced in variegated ways across the lifespan. By covering a variety of phenomena, from biopics, music by the elderly, and artefacts, among other, they all contribute to further the understanding of memory as a cultural process always in the making - situated in particular contexts, and shaped by its material conditions of existence.

Imaginary Women, Imaginary Audience: Gender and Top 40 Radio in Montréal - Maki, Christine (Women in Radio: Unfiltered Voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audi ence. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit wom en’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.

Mapping as a Complementary Perspective on the Dynamics of Participation in a City’s Musical Life - Marcoux-Gendron, Caroline; De Alvarenga, Bernardo (Bulletin of Sociological Methodology/Bulletin de Méthodologie Sociologique, 2020)
Maps and map-making have been used in a range of research about musical phenomena in cities. Yet, most of these studies focus on musicians; few have attempted to understand how people take part in a city’s musical life in terms of event attendance. Likewise, little has been said about the attendance habits of immigrants, despite the quick transformation of urban populations due to the expansion of human migration. Approaching a subject that has received so little attention as the dynamics of participation of immigrants in a city’s musical life therefore requires an inventive research design. Building from a methodology combining semi-structured interviews and observation, I used maps and map-making to deepen the analysis of North African immigrants’ cultural practices in Montreal. Trying to give a spatial legibility to their musical activities in the city generated many technical and theoretical concerns, but was also helpful for reflecting on the project differently and highlighting some characteristics of the data that were not obvious from the initial fieldwork. In brief, maps and map-making proved to be efficient complementary tools to ethnography, bringing new insights and raising new queries about the practices being considered.
Keywords: audiences; cartes; cartographie; cities; cultural participation; cultural practices; ethnographie; ethnography; immigration; map-making; maps; music; musique; participation culturelle; pratiques culturelles; publics; villes

Shekhinah in the Music Videos of Leonard Cohen - Měsíc, Jiří (From Page to Screen: Modification and Misrepresentation of Female Characters in Audiovisual Media, 2020)

Tuning a Room: Designs for Hearing According to Nancy Tobin - Rewa, Natalie (Canadian Theatre Review, 2020)
In this review, I discuss the architectonics of sound composition according to sound artist and designer Nancy Tobin. This chapbook advocates for a comprehensively integrated presence of a sound artist in the processes of rehearsal and espouses a dramaturgy of hearing. Tobin’s distinction between hearing and listening gives forth onto a series of self-studies of her experience of spatial and temporal arrangements presented in the form of e-mails to mentees. Her appreciation for the acoustics of the performance space extends to the composition of sound to be heard (on occasion as boldly interventionist) and the technologies of broadcasting it: the choice and placement of speakers, as well as their interaction with the performers. Tobin argues for a definition of sound composition for performance as a complex collaboration with the production—curatorial in terms of the space of ephemerality. My review concurs with the efficacy of her approach by my recognition of the moments in productions that have remained as some of the most memorable of my theatregoing.
Keywords: Nancy Tobin; acoustic space; rehearsal processes; sonic/acoustic dramaturgy; sound artist; speaker specifications and broadcasting sound

Gendered Pirates: Women’s Roles in Temporary Autonomous Radio - van der Zon, Marian (Women in Radio: Unfiltered Voices from Canada, 2020)
Taking over the airwaves in a small neighbourhood in Montréal was the first step in the creation of the Temporary Autonomous Radio, a pirate station open to women and serving its community when needed. From Montréal, founder Marian van der Zon moved TAR to the West Coast, temporarily on the airways in Victoria, Nanaimo, and rural Vancouver Island. Pirate radio under five watts is usually overlooked in Canada. Beyond music festivals, TAR serves to provide information about issues not often covered in mainstream media. Most importantly, it allows women to be themselves and explore their identities through a non-gendered medium